Penyusunan Kamus Tematik Bahasa Inggris bagi Santri sebagai Penunjang Program English Day di Pesantren: Compilation of English Thematic Dictionary for Students as Support for English Day Program in Islamic Boarding Schools - Yeni Suprihatin; Rika Dartiara; Desy Awal Mar’an; Eka Yuniasih (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2024)
Language learning can be seen from its skills in developing productive skills, namely writing and speaking. English speaking skills are one of the leading activities developed in modern Islamic boarding schools. English speaking skills will be easier to achieve if the facilities and infrastructure are met, such as complete learning books, media and other,r supporting facilities. Therefore, no special books or dictionaries support the English Day program at Islamic Boarding Schools. This study offers a solution to develop an English Thematic Dictionary product that students can use. This study uses a research and development method called Research and Development (R & D). This method produces products and tests the effectiveness of the product. There are two main steps, namely the exploration and development stages. In the observation stage, researchers review the literature, conduct field studies, and analyze needs. Then, in the development stage, researchers develop prototypes, perform product validation with experts, and conduct trials. The specifications of this product are the English Thematic Dictionary titled "AL Ma'had English Guide; A Thematic Dictionary." This dictionary is compiled in Indonesian-English bilingual based on themes by sorting the vocabulary alphabetically and prioritizing Islamic values in each unit. The specifications for developing this product include vocabulary, expressions, idioms, proverbs, or expressions closely related to students' daily lives in Islamic Boarding Schools, especially emphasizing Islamic values ?? and students' character. Material experts, media experts, and language experts review the assessment of the dictionary. After the developed product is validated and revised based on input and suggestions from the validator, the developed English thematic dictionary is declared to have a practical product value. It is suitable for use (effective).